Stability and Construction Control of Existing Steel Truss Roof Reconstruction Projects: Case Analysis and Numerical Simulation - Guanghao Mai; Weijian Kuang; Dongming Zhu; Yao Song; Xiaozhou Zou; Yu Qiu; Zhe Xiong (Buildings, 2025)
Many existing structures require retrofitting and reinforcement due to aging and damage. The stability of the retrofitted structure is key to the retrofitting scheme, while construction safety during the retrofitting process is another crucial consideration. This study proposed an evaluation method for assessing the stability and construction process of steel structure retrofitting projects based on an ANSYS finite element analysis. By establishing a nonlinear finite element model of a retrofitted gymnasium roof truss structure, the overall stability of the system was systematically verified. The dynamic simulation of demolition and retrofitting procedures was conducted using the birth-and-death element technique, and a comprehensive safety assessment framework covering the entire construction process was developed. The case analysis demonstrated that this method can simulate the redistribution of internal forces during component demolition and identify potential risks. The effectiveness of the retrofitting strategy was evaluated by comparing the nonlinear stability coefficients of the structure before and after retrofitting, indicating improved performance within the scope of the finite element model. The research results demonstrated the feasibility of incorporating modeling, simulation, and assessment in retrofitting projects and provided a reference for similar retrofitting projects.